In vitro antiradical, cytotoxic, genotoxic and phytochemical properties of Astragalus compactus Lam. subsp. compactus - Keser, Serhat; Çiftçi, Ebru Bahar; Keskin, Tuba; Tekin, Suat; Kaygılı, Omer (Niyazi BULUT, 2025)
In this study, it was aimed to determine the antiradical, cytotoxic, genotoxic and phytochemical compounds of ethanol, methanol and water extracts of Astragalus compactus Lam. subsp. compactus (guni) plant grown in Elazig. Antiradical activity of the plant was determined against ABTS, DPPH, and OH radicals, and the cytotoxic and genotoxic activities were determined against A2780 and MCF-7 cell lines with MTT and Comet assays. All extracts of A. compactus in all the radical scavenging tests showed lower antiradical activity than the standard antioxidant BHT. However, it was determined that this plant is rich in some important phytochemical compounds, such as phenolic, flavonoid, proanthocyanidin, and phytosterols. DNA damage studies of A. compactus extracts were carried out by the Comet assay and all the results showed that cell death occurred for the A2780 cell lines.
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer)